CNSC-32. ACTIN SUBUNIT STRUCTURAL DIVERSITY IN SHH MEDULLOBLASTOMA: IMPLICATIONS FOR CANCER BIOLOGY AND NEURODEVELOPMENT. (14th November 2022) - Beaulieu, Jamie; Knapp, David; Picard, Daniel; Remke, Marc; Sadikot, Abbas; Diaz, Roberto
Abstract: BACKGROUND: Altered expression of actin subunits is found in multiple cancers. Alpha-cardiac actin (ACTC1) is expressed in sonic hedgehog medulloblastoma (SHH MB) and regulates both cell survival and migration. We hypothesized that cardiac actin has a unique structural and functional role in SHH MB and may be expressed in post-natal granule cell progenitors (GCPs) which share similar gene expression profiles. METHODS: Actin subunit protein expression (ACTC1, ACTB, ACTG1, and ACTA2) was evaluated by mRNA expression profiling within established datasets and across MB cell lines by Western blot (WB). Immunofluorescence microscopy was performed to assess intracellular actin subunit localization. The composition of each subunit in filamentous (F-) actin was evaluated. Furthermore immunoprecipitation of filamentous ACTC1 was performed to assess protein-protein interactions. The ratio of F-actin to globular (G-) actin was determined by WB in SHH MB cells exposed to mitotic inhibitor. Cell viability was determined by colony formation following over-expression of dominant-negative mutant ACTC1 (P116C & G247D). RESULTS: ACTC1, ACTG1, and ACTB are the predominant actin subunits in SHH MB. Immunofluorescence microscopy demonstrated co-localization of ACTC1 with ACTG1 and ACTB but not ACTA2. ACTC1 showed a unique cortical localization pattern. Post-natal MATH1 positive mouse GCPs (P3-5) demonstrate similar distribution of ACTC1 in cortical F-actin. WB analysis of ACTC1 pulldown from SHH MB cell F-actin fractions showed co-precipitation with ACTG1 and ACTB but not ACTA2. ACTC1 F-actin to G-actin ratio is maintained in cells that show resistance to mitotic inhibition. Expression of mutant ACTC1 G247D resulted in reduced cell survival. CONCLUSIONS: ACTC1 subunit is incorporated into F-actin in SHH MB and GCPs. Filamentous ACTC1 forms a protein complex with ACTG1 and ACTB. Disruption of ACTC1 polymerization results in reduced cell survival. These findings suggest a functional role of ACTC1 in both SHH MB and in GCPs which are important in cerebellar development.